Nieuwjaarsrecepties, afscheid Timmer, Herengracht 262-266, 40 jaar IISG, IALHI conferentie, Keizersgracht 264
Nieuwjaarsrecepties, afscheid Timmer, Herengracht 262-266, 40 jaar IISG, IALHI conferentie, Keizersgracht 264.